Kakawin dan Hikayat: Refleksi Sastra Nusantara - Bambang Widiatmoko (Masyarakat Pernaskahan Nusantara, 2011)
This review discusses an anthology edited by Abdul Hadi W.M. et al., which compiles research chapters from 13 contributors aimed at revitalizing public awareness of Maritime Southeast Asia’s (Nusantara) rich intellectual and literary heritage. The volume spans classical Old Javanese literature to late 19th-century works. Key discussions include Mpu Kanwa's Arjunawiwaha, analyzed by Abdul Hadi W.M., which highlights its unique poetic meters (kakawin), aesthetic departures from Sanskrit models, and the synthesis of Tantric philosophy (dharma, artha, kama, moksa) with quietude (santarasa) as an act of worship (yantra). Furthermore, the review outlines Puji Santosa's examination of Javanese didactic macapat texts (Wedhatama, Wirawiyata, Tripama) as reflections of elite priyayi values and spiritual perfection, and Suwanti's study on Hikayat Panji Semirang, which illuminates traditional Javanese views on romance, social nobility, and marital education. Additional essays explore Minangkabau perspectives on Malay history (Mu'jizah), Acehnese literary traditions (S. Amran Tasai), frame stories like Hikayat Maharaja Ali (Sastri Sunarti), the mythologized history of Syarif Hidayatullah of Cirebon (Siti Zahra Yundiafi), and Islamic attitudes in Panji Wulung (Abdul Rozak Zaidan).